PENGGUNAAN PBL UNTUK MENINGKATKAN HASIL BELAJAR PPKn SISWA KELAS X SMA MUJAHIDIN PONTIANAK - Jasmine, Khariza Arnita; Sulistyarini, Sulistyarini; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract                                                              This research aims to improve student learning result by using the Problem Based Learning (PBL) learning model in Civic Education subjects. This is a classroom action research with the descriptive method. The research was conducted at the senior high school Mujahidin Pontianak, enaging 31 of 10th -grade Social 3 students as the research subject. Data collection techniques used were measurement techniques, direct observation techniques, and documentary study techniques with data collection tools used were learning result tests and observation sheets. The collected data were analyzed by calculating the average and the percentage. Each cycle consists of 4 stages, named planning, implementation, observation and reflection. The results showed that, in the Cycle I, the average student learning result was only 63,22 with the number of students reach the minimum completeness criteria (KKM) was 3 students or 9.67%.respectively, the average result in Cyle II and Cycle III are 71,29 and 85,28 with the number of students passing the KKM as many as 13 and 27 or 42,00% and 87,00% in percentage. Based on the analysis, it shows that PBL model can improve learning result to the 10th –grade student of Social 3 in Senior High School Mujahidin Pontianak in Civic Education subject.Keyword: Learning Result, PBL, Used